Epidemic, Endemic, or Stewart-Bluefarb? When Several Forms of Kaposi Seem to Dispute Paternity - Hugues Adegbidi; Bérénice Dégboé; Fabrice Akpadjan; Nadège Agbessi-Mekoun; Christiane Koudoukpo; Alida Kouassi; Félix Atadokpede (Hindawi Limited, 2020)
The role of human herpes virus 8 (HHV8) is demonstrated in the occurrence of Kaposi's disease, but the role of cofactors is still hardly known. We report a case of Kaposi's disease which occurred 10 years after a local trauma in an HIV-positive patient from Central Africa. A 38-year-old female, from and living in Central Africa, consulted for angiomatous papulo-nodules associated with purple-colored macules and painful lymphoedema of the right leg and foot that had been developing for 6 months. She reported a history of posttraumatic lymphoedema of the affected limb as a result of a road accident that occurred ten years earlier. The mucous were healthy. There was no sign of systemic lesions. The diagnosis of Kaposi's disease was evoked with, in differential, a Stewart-Bluefarb syndrome-type of pseudo-Kaposi and an epidemic Kaposi disease. Retroviral serology was positive to HIV1 with a CD4 count of 600 cells/mm3. Histopathology of the lesions and duplex ultrasonography could not be performed. The rest of the biological assessment was without particularity. The diagnosis of epidemic Kaposi's disease associated with cofactors involved in endemic Kaposi's disease and Stewart-Bluefarb syndrome was retained. An antiretroviral treatment (emtricitabine, tenofovir, and efavirenz) allowed to obtain after 6 months a noticeable improvement of the lesions and a disappearance of the pain with however the persistence of a residual lymphoedema. This is a special case of Kaposi's disease that seems to involve several factors. The role of cofactors in Kaposi's disease remains to be elucidated.